Partisipasi Masyarakat Pada Pembangunan Pariwisata di Desa Ngargogondo, Magelang, Jawa Tengah - Stefani Ekky Puspa Dewi; Aldi Herindra Lasso (Jurnal Pariwisata Terapan, 2022)
Community participation is an important element in the development of community-based tourism. However, in practice, people participation is not easy to encourage because the community itself consists of various stakeholders. Presenting a case study of community participation in Ngargogondo Village, this study elaborates on the role of rural communities in tourism development. Through a qualitative approach with in-depth interview in data collection, this study analyzes the forms of participation of the Ngargogondo Village community in local tourism development. The findings show that three community groups in Ngargogondo Village carry out different levels of participation: citizen control, consultation, and manipulative. This shows that the community is heterogeneous, thus, community-based development in a village should be implemented with different approaches that adapt to the diversity of stakeholders in it.